EXPERIMENTAL DESIGNS IN SENTENCE PROCESSING RESEARCH: A Methodological Review and User’s Guide - Keating, Gregory D.; Jegerski, Jill (Studies in second language acquisition, 2015)
Since the publication of Clahsen and Felser’s (2006) keynote article on grammatical processing in language learners, the online study of sentence comprehension in adult second language (L2) learners has quickly grown into a vibrant and prolific subfield of SLA. As online methods begin to establish a foothold in SLA research, it is important that researchers in our field design sentence-comprehension experiments that adhere to the fundamental principles of research design typical of sentence processing studies published in related subfields of the language sciences. In this article, we discuss and review widely accepted principles of research design for sentence processing studies that are not always followed in L2 sentence processing research. Particular emphasis is placed on the design of experimental items and distractors, the choice and design of the poststimulus distractor task, procedures for presenting stimuli to participants, and methods for trimming and analyzing online data, among others.